PD(L)1 Inhibitors Plus Lenvatinib Vs Atezolizumab Plus Bevacizumab Combined With HAIC for Unresectable HCC: A Propensity Score Matching Study - He Z; Chen H; Liang C; Tang X; Jiang L; Xie F; Liu Q; Zheng Y (ImmunoTargets and Therapy)
Zhaoqian He,1– 3,* Hua Chen,1– 3,* Chen Liang,1– 3,* Xiang Tang,1– 3 Lingmin Jiang,1– 3 Feihu Xie,1– 3 Qi Liu,1– 3 Yun Zheng1– 3 1Department of Liver Surgery, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, 510060, People’s Republic of China; 2Collaborative Innovation Center for Cancer Medicine, State Key Laboratory of Oncology in South China, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, 510060, People’s Republic of China; 3Guangdong Provincial Clinical Research Center for Cancer, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, 510060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun Zheng; Qi Liu, State Key Laboratory of Oncology in South China, Sun Yat-Sen University Cancer Center, Collaborative Innovation Center for Cancer Medicine, Guangzhou, Guangdong, 510060, People’s Republic of China, Email zhengyun@sysucc.org.cn; liuqi9@sysucc.org.cnPurpose: To compare the clinical outcomes of different systemic therapies, specifically PD(L)1 inhibitors plus Lenvatinib versus Atezolizumab plus Bevacizumab, when combined with hepatic arterial infusion chemotherapy (HAIC) based on the FOLFOX regimen (oxaliplatin, fluorouracil, and leucovorin) as first line treatment for unresectable hepatocellular carcinoma.Patients and Methods: This real-world retrospective study enrolled 294 patients with unresectable HCC. All patients received HAIC in combination with either PD(L)1 inhibitors plus Lenvatinib (PLEN-HAIC) or Atezolizumab plus Bevacizumab (AT-HAIC). Propensity score matching (PSM) was performed to balance patient characteristics. The overall response rate (ORR), progression-free survival (PFS), and overall survival (OS) were compared.Results: After PSM, 80 and 130 patients received AT-HAIC and PLEN-HAIC, respectively. No significant differences were found in ORR between the AT-HAIC and PLEN-HAIC groups (50.0% vs 40.0% per RECIST, p = 0.202; 60.0% vs 57.7% per mRECIST, p = 0.853). Both groups showed similar disease control rates. Median PFS was 14.3 months for PLEN-HAIC versus 8.8 months for AT-HAIC (p = 0.018). Median OS was significantly better in the PLEN-HAIC group (p = 0.045, both not reached). Subgroup analysis revealed that Lenvatinib showed a better OS compared to Bevacizumab when combined with HAIC and PDL1 inhibitors (p = 0.023).Conclusion: PLEN-HAIC offers significant survival benefits over AT-HAIC in advanced HCC. Given its remarkable efficacy, PLEN-HAIC could be a promising first-line option for unresectable HCC.Keywords: hepatocellular carcinoma, immunotherapy, hepatic arterial infusion chemotherapy, propensity score matching, real-world study